Peripheral Tangible Interaction by Analytic Design - Edge, Darren; Blackwell, Alan (TEI 2009 Conference on Tangible and Embedded Interaction, 2009)
Tangible User Interfaces (TUIs) are commonly accepted as those in which the configuration of physical objects embodies digital system state, providing “graspable” digital media that can be manipulated in the focus of users’ attention. In this paper we offer an alternative perspective on the use of tangibility in interaction, in which meaning is created not through precise manipulations of a computationally-interpreted spatial syntax, but through imprecise interactions with independently meaningful, digitally-augmented physical tokens. Users are free to arrange such tokens around the periphery of their workspace, away from their normal centre of attention, ready to selectively and fluidly engage them in loosely related, dispersed episodes of use. We call this concept “peripheral tangible interaction”, and in this paper we describe both our analytic approach to designing a personal desktop TUI supporting such an interaction style, and user responses to its analytically-inspired features during extended deployment in a real office context.